2021
DOI: 10.3390/cancers13246175
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine in Pancreatic Cancer: Current Status and Future Opportunities for Overcoming Therapy Resistance

Abstract: The development of drug resistance remains one of the greatest clinical oncology challenges that can radically dampen the prospect of achieving complete and durable tumour control. Efforts to mitigate drug resistance are therefore of utmost importance, and nanotechnology is rapidly emerging for its potential to overcome such issues. Studies have showcased the ability of nanomedicines to bypass drug efflux pumps, counteract immune suppression, serve as radioenhancers, correct metabolic disturbances and elicit n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 270 publications
0
12
0
Order By: Relevance
“…4 , various nanomedicines have shown pharmacological efficacy in subcutaneous tumor-bearing mouse models; however, there are few reports in pancreatic cancer models 28 , 29 . One of the reasons is that angiogenesis occurs in subcutaneously implanted tumors, which facilitates the EPR effect; however, tumors formed in the pancreas are covered with stroma and have few blood vessels making it difficult to demonstrate an EPR effect 28 , 29 . KS-58 NPs showed a clear pharmacological effect not only in subcutaneous tumor-bearing mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 , various nanomedicines have shown pharmacological efficacy in subcutaneous tumor-bearing mouse models; however, there are few reports in pancreatic cancer models 28 , 29 . One of the reasons is that angiogenesis occurs in subcutaneously implanted tumors, which facilitates the EPR effect; however, tumors formed in the pancreas are covered with stroma and have few blood vessels making it difficult to demonstrate an EPR effect 28 , 29 . KS-58 NPs showed a clear pharmacological effect not only in subcutaneous tumor-bearing mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The application of nanotechnology to the medical field, termed nanomedicine, [31][32][33] is enabling novel treatments to enter preclinical and clinical trials, with the aim of overcoming the limitations shown by conventional therapies: to mention but a few, light-and ultrasound-triggered minimally invasive techniques such as sonodynamic and photodynamic therapy have recently been applied to PDAC. [34,35] In addition to that, an ever-increasing knowledge of this particularly resistant tumor and its hallmarks has progressively led to the adoption of innovative and smart approaches: targeted therapies to avoid multidrug resistance and systemic toxicity, [36,37] stromal therapies aimed at a TME and vessel normalization, [38][39][40][41] the use of exosomes as nanocarriers for gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of “targeted drug delivery” in cancer promises to focus the effects of anticancer agents onto the cancer cells themselves, avoiding, as much as possible, cytotoxic effects on healthy, non-cancerous cells. This would not only aim to minimize systemic side effects but could also enable the delivery of higher drug doses locally and help to act against mechanisms of drug resistance [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%